Mayoral Influence on Participatory Budgeting in Lithuania during Covid-19 - Valentina Burkšienč—; G. Burbulytč—-Tsiskarishvili; Jaroslav Dvorak (Emerging Science Journal, 2022)
The paper deals with two topics: Participatory Budgeting (PB) and mayoral impact on its success. Its theoretical background is rooted in the interrelation of the discourse of PB and characteristics of mayors as city leaders. The paper analyzes articles revealing personal, social and political characteristics of mayors and their impact on civic governance. The scope of collected characteristics was researched with a view on how they impact succession and the resilience of PB. The idea behind this analysis was not only to reveal mayoral characteristics and their impact on PB in general, but to test them against the background of the Covid-19 pandemic as an example of an external crisis. PB practice in Lithuanian municipalities was researched. Qualitative semi-structured interviews were conducted with mayors or their subordinates and helped to reveal the mayors' role and impact on PB resiliency. Relevant statistical data was collected and analyzed in order to obtain the specific characteristics. The results proved the impact of mayors' social and personal backgrounds on PB resiliency, but during challenging times or even crises, political affiliation, interrelation with the council or administrative and political skills are supportive factors. The paper suggests that mayors cannot ensure the persistence of PB alone when finances are scarce during times of crisis. Doi: 10.28991/esj-2022-SPER-011 Full Text: PDF